(3TQM GdbUjOI GdMejQjIs - (3fThGf Hf SYjO GdMejQj, CHh SYjO,J (B573 (3g` s
(3ChdgG (B:s
(3bGd GdYdGeI fThGf GdCeQ LOhgh ZjQ ehGM aGNJQ dfaSc UGdMkG jGUGM s
(3bUjOI COHjI JGQjNjI ai GdhYX GdJPcQ HCMhGd GdCee GdZGHQI hGdCfHjGA GdSGdaIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B20 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B86s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 - (3U (B491 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3COH (B580) s
Keywords: (3GdCOHs